CALCIUM PYROPHOSPHATE DIHYDRATE CRYSTAL DEPOSITION DISEASE (PSEUDOGOUT): CASE REPORT - Berna Yıldız; Hatice Bodur (Archives of Rheumatology, 2006)
Presence of intra-articular calcifications (chondrocalcinosis) is a common finding in older individuals. Patients with calcium pyrophosphate dihydrate deposition disease (CPPD) may present with a number of clinical presentations such as acute gout, rheumatoid arthritis, osteoarthritis, and neuropathic joint. The joints most frequently involved are the knee, wrist, elbow, and hip. The diagnosis of pseudogout may be based on the clinical presentation, pattern of joint involvement and radiographic intra-articular calcifications. Diagnosis is confirmed by the demonstration of CPPD crystals in microscopic examination of synovial fluid. In this report we present three cases with CPPD deposition disease. (Rheumatism 2006; 21: 34-6)